Bacterial Species in Engineered Living Materials: Strategies and Future Directions - Hu Wang; Chunzhong Li; Yanmin Wang; Huanming Zhang (Microbial Biotechnology)
ABSTRACT In recent years, there has been a notable increase interest in engineered living materials (ELMs) owing to their considerable potential. One key area of research within this field is the utilisation of various species of bacteria to create innovative living materials. In order to accelerate the advancement of bacterial‐based living materials, a systematic summary of bacterial species and their design strategies is essential. Yet, up to this point, no applicable reviews have been documented. This review offers a concise introduction to living materials derived from bacteria, delves into the strategies and applications of each bacterial species in this realm, and provides perspectives and future outlooks in this field.